Time response analysis of control systems - Africa, Aaron Don M. (Animo Repository, 2019)
In time response analysis, there are many various sub-topics that are included. Some of these topics which will be discussed in this research paper are the different types of test signals, transient analysis and steady-state analysis concepts, first-order transient response analysis, second-order transient response analysis, higher-order LTI system transient response analysis, and under high order LTI system transient response analysis are the effects of adding poles and zeros and non-minimum phase for zeros, and lastly under systems is the effect of nonlinearities. © 2019, World Academy of Research in Science and Engineering. All rights reserved.